Enhancing Cognitive and Argumentation Skills through Integration of Argument-Driven Inquiry and the Scientific Method in Physics Education - Nurjannah, Nurjannah; Sani, Nurul Kami; Haeruddin, Haeruddin; Kade, Amiruddin; Khuzaimah, Andi Ulfah (Universitas Muhammadiyah Makassar, 2025)
Developing students’ cognitive abilities and scientific argumentation skills is critical in physics education, yet traditional teacher-centered approaches often fail to achieve these goals. This study investigates the impact of integrating the Argument-Driven Inquiry (ADI) model with the scientific method on students’ conceptual understanding and argumentation quality. A quasi-experimental pretest–posttest control group design was employed involving 64 Grade XI science students from a senior high school in Palu, Indonesia. Participants were assigned to an experimental group (ADI + scientific method) and a control group (ADI only) through a cluster random sampling method. Both groups studied the topic of heat and temperature over three sessions. Cognitive ability was measured using a validated multiple-choice test targeting understanding (C2), application (C3), and analysis (C4), while argumentation skills were assessed using an open-ended test based on Toulmin’s Argument Pattern. Results showed that the experimental group achieved higher normalized gains in cognitive ability (0.65, medium) compared to the control group (0.37, medium), and in argumentation skills (0.76, high) compared to 0.66 (medium). A strong positive correlation (r = 0.61, p < 0.001) was observed between cognitive and argumentation gains, indicating a reciprocal relationship. The novelty of this study lies in embedding scientific method phases into ADI’s discourse structure, producing measurable synergy between conceptual and epistemic outcomes. The findings contribute to physics education by offering an empirically supported instructional model that fosters both content mastery and scientific reasoning, providing a framework for enhancing scientific literacy in secondary classrooms.